Toxic Prisons? Local Environmental Quality and the Wellbeing of Incarcerated Populations - Moran, Dominique; Jordaan, Jacob A.; Jones, Phil I. (Land (Basel), 2024)
A growing body of scholarship draws attention to prisons and environmental justice, pointing out the propensity for prisons to be located on contaminated sites and to be in close proximity to polluting industries, as well as for prisons themselves to contribute to local environmental degradation. Prisoners’ immobility renders them unable to relocate away from harmful environments, and there are now numerous suggestions that their wellbeing suffers as a result of the poor quality of many local environments. However, since a relationship between environmental quality and prisoner wellbeing is yet to be robustly demonstrated, there is currently no firm evidence base from which to argue for positive change. This paper therefore examines the effect of the environmental quality of the locations of prisons, approximated as the presence of greenspace in the immediate vicinity of prisons, local species biodiversity and local levels of air and noise pollution, on wellbeing outcomes in a set of prisons in England and Wales. It finds that good environmental quality, in the form of high biodiversity and/or low air pollution, enhances the already-recognized positive effects of greenspace on the wellbeing of incarcerated populations. On the basis of these findings, this paper makes evidence-based policy recommendations intended to enhance the wellbeing of incarcerated populations.